Covid-19: Impacts on Tourism in Bako National Park and Survival Strategies of Local Tourism Operators - Nur Anisah, Mohamad Junaidi; Haslina, Hashim (Secholian Publication, 2023)
The Covid-19 pandemic has caused havoc in every field globally, including the second highest industry, tourism. This paper focuses on the impacts resulting from the pandemic on tourism activities in Bako National Park and the local communities who are dependent on this natural attraction as an important source of income. Using the case study methodology, in-depth interviews were conducted with six tourism operators in Bako National Park to gauge how the pandemic impacted the tourism activities socially, economically, and environmentally. This paper unpacks how they coped with the associated challenges to stay afloat while waiting for the border to fully reopen. It is found that different types of tourism operators employ different survival strategies depending on the resources they have. While certain strategies could offset the immediate effects of the lockdown, some are meant for survival in the future.